2020
DOI: 10.20529/ijme.2020.70
|View full text |Cite
|
Sign up to set email alerts
|

Must there be a “war” against coronavirus?

Abstract: The ongoing Covid-19 pandemic is marked not only by rapid spread of the causative virus, SARS CoV-2, but also by the spread of warlike narratives. Leaders of different countries have compared the pandemic response to being at war. In this argument paper, the authors take the stance that frequent public pronouncements of metaphors of war do more harm than good, especially when they percolate through the societal psyche and the healthcare system. We describe how the narrative of war has further dented social coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Of significant, immediate concern is the militarisation and use of 'war narratives' that compare COVID-19 with a battle and relate the pandemic to being at war, referring to 'the enemy', with calls to 'save the economy' and essential workers labelled 'frontline warriors'. 6 Military capabilities can contribute in mobilising logistics and infrastructure. However, in many countries globally, state security forces and not public health workers or local law enforcement personnel have been deployed to communities to contain the spread of COVID-19.…”
Section: Evidence Of Harms In An Authoritarian Biosecurity Responsementioning
confidence: 99%
“…Of significant, immediate concern is the militarisation and use of 'war narratives' that compare COVID-19 with a battle and relate the pandemic to being at war, referring to 'the enemy', with calls to 'save the economy' and essential workers labelled 'frontline warriors'. 6 Military capabilities can contribute in mobilising logistics and infrastructure. However, in many countries globally, state security forces and not public health workers or local law enforcement personnel have been deployed to communities to contain the spread of COVID-19.…”
Section: Evidence Of Harms In An Authoritarian Biosecurity Responsementioning
confidence: 99%
“…These developments were thought to affect the patients’ thoughts about the COVID-19. Besides, the aim to empower patients using war metaphors could make negative situations on patients, such as feelings of vulnerability, passivity, and guilt when the disease progressed (Rohela et al, 2020). This study showed that the patients expressed the treatment process either directly through the metaphor of war or suffering, fear, and death.…”
Section: Discussionmentioning
confidence: 99%
“…Like many other global leaders, Modi often alluded to the term 'war'. Phrases such as 'war against coronavirus', '#IndiaFightsCovid19', 'COVID warriors', and 'Corona fighters' have emerged as common terms that were used intensively in health communication and in media narratives (Rohela et al, 2020). Healthcare workers and doctors, and even the police personnel who were implementing the lockdown, were 'deployed' in the frontline and were termed the 'frontline warriors'.…”
Section: The Curious Case Of Covid-19mentioning
confidence: 99%
“…Public pronouncements replete with war metaphors were perhaps necessary to boost public morale and unity. Such messages provided a ready recourse for health communication, given the low levels of scientific literacy among the general public in India (Landau et al, 2018;Rohela et al, 2020). Some researchers argue that the negative consequences of using such metaphors for COVID-19 could have resulted in the creation of an epidemic of fear, discrimination, and stigma against those who were on the frontline or those who contracted the virus; widening of the gap between patients/people and health workers; and acceptability of overmobilisation of resources in one direction and the resultant collateral damage (Rohela et al, 2020).…”
Section: The Curious Case Of Covid-19mentioning
confidence: 99%